The Influence of Dietary Lysine on Yellow Perch Female Reproductive Performance and the Quality of Eggs - Kwasek, Karolina; Dabrowski, Konrad; Nynca, Joanna; Takata, Rodrigo [UNESP]; Wojno, Michal; Wick, Macdonald (Taylor & Francis Inc, 2014)
The objectives of this study were to (1) evaluate if dietary lysine (Lys) has an effect on the free amino acid (FAA) pool of Yellow Perch Perca flavescens eggs, and (2) determine how dietary Lys influences the reproductive performance and eggs fertilization rate (embryo survival) of female Yellow Perch. Two-year-old Yellow Perch of initial size of approximately 75 g were randomly distributed into six 400-L tanks at 32 +/- 1 fish per tank. This experiment included two wheat gluten-based diets in triplicate Lys-deficient ([-] Lys) and Lys-supplemented ([+]Lys; 2.23% in dry feed) diets. Females from the reference group were fed a commercial diet. Females from reference, (+) Lys, and (-) Lys groups were stripped and their eggs divided into 0.4-1.2-g portions and mixed with sperm (21.4 +/- 4.3 mu L) from either reference, (+) Lys, or (-) Lys males. The mean weight of Yellow Perch females and mean total weight of ovulated eggs were the greatest in the reference group compared with both (+) Lys and (-) Lys groups. There were no differences in the ratio of weight of eggs to female body weight as well as egg size among groups. There was no difference among treatments in the concentration of free amino acids except glutamic and aspartic acids in Yellow Perch eggs. There was significant effect of female dietary treatments on the egg fertilization rate averaged across all males. The higher fertilization rate was observed in the reference and (+) Lys groups compared with the (-) Lys group. The effect of female dietary treatment on the egg survival was also dependent on the dietary treatment of males.